2015
DOI: 10.1038/sc.2015.92
|View full text |Cite
|
Sign up to set email alerts
|

Two-year survival following discharge from hospital after spinal cord injury in Bangladesh

Abstract: Study design: Mixed retrospective-prospective cohort study. Objectives: To determine 2-year survival following discharge from hospital after spinal cord injury in Bangladesh. Setting: Bangladesh. Methods: Medical records were used to identify all patients admitted in 2011 with a recent spinal cord injury to the Centre for Rehabilitation of the Paralysed, a large Bangladeshi hospital that specialises in care of people with spinal cord injury. Patients or their families were subsequently visited or contacted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 14 publications
0
53
2
Order By: Relevance
“…These data align with the mortality data from our larger cohort, which indicated that 56% of the 55 deaths in the first 2.5 years following discharge were due to pressure ulcers. 8 Pressure ulcers are clearly one of the biggest health risks for people with SCI in LMICs. 22,23 The participants in this cohort had all received comprehensive education about low cost strategies to prevent pressure ulcers during their inpatient rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data align with the mortality data from our larger cohort, which indicated that 56% of the 55 deaths in the first 2.5 years following discharge were due to pressure ulcers. 8 Pressure ulcers are clearly one of the biggest health risks for people with SCI in LMICs. 22,23 The participants in this cohort had all received comprehensive education about low cost strategies to prevent pressure ulcers during their inpatient rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The methods and survival data have been published elsewhere. 8 In brief, all patients admitted with SCI to a large hospital in Bangladesh in 2011 were followed up by telephone in 2014. Consequently, the study was a mixed retrospective-prospective cohort study.…”
Section: Materials and Methods Designmentioning
confidence: 99%
“…We had similar success finding participants two years after discharge in our earlier cohort study. 7 In that trial we were able to locate and determine outcomes for 97% of 350 participants. Our success in following up participants is in contrast to the low follow-up rates often reported in studies conducted in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure ulcers for this group of people are a major cause of mortality and misery and receive very little research attention. 6,31 The primary aim of this trial was to determine the effects of a 12-week telephone-based pressure ulcer management programme on pressure ulcer size in people with SCI. The results for the primary outcome (size of pressure ulcer) failed to provide a clear answer to our research question; however, the results do not rule out the possibility that advice about pressure ulcer management provided over the telephone may be a worthwhile intervention (mean betweengroup difference = 2.3 cm 2 ; 95% CI − 0.3 to 4.9).…”
Section: Discussionmentioning
confidence: 99%
“…5 A large cohort study from Bangladesh reported that one in five people with SCI who were wheelchair dependent had died within 2 years of discharge from hospital, mostly from pressure ulcers (2-year survival was 81%; 95% confidence interval (CI) 76-86%). 6 Given the high rates of postdischarge mortality in LMICs, finding effective, low-cost and locally applicable treatment options for the management of pressure ulcers is a key part of improving levels of care for people with SCI globally. 5 There is a large divide between the management of pressure ulcers in high-income countries compared with the management in LMICs.…”
Section: Introductionmentioning
confidence: 99%